REFORMASI PERPAJAKAN - Lusy Suprajadi (Bina Ekonomi, 2000)
The Five tax laws amended were the laws on income tax, on value added tax and luxury sales tax, on general rules and procedures of taxation, on tax collection by distress warrant and on the transfer tax on land and buildings. These amendments were designed to broaden the tax base, improve tax administration, and enhance a fairer distribution of the tax burden, a higher level of tax compliance, hence larger tax receipts.